Prognostic and Predictive Significance of PD-L1 Expression in Non-Small Cell Lung Cancer Patients: A Single-Center Experience - Hacı ARAK; Aydın AYTEKIN; Ozlem CANOZ; Metin OZKAN (Federation of Turkish Pathology Societies, 2021)
Objective: To investigate the prognostic and predictive value of PD-L1 expression in operated non-small cell lung cancer (NSCLC) patients and to analyze its relationship with clinicopathological factors. Material and Method: A total of 90 patients with operable NSCLC were included in this retrospective single center study. Tumor blocks of patients were stained immunohistochemically with PD-L1 polyclonal antibody. When evaluated immunohistochemically and statistically, patients with tumor staining percentage of ≥5%, those with +2 and +3 membranous staining intensity, and those with ≥50% H-Score were considered positive. The relationship between PD-L1 expression status and clinicopathological features in addition to the prognostic effect of PD-L1 on survival were statistically analyzed. Results: The frequency of PD-L1 expression was 37%, 15% and 5% according to the staining percentage, staining intensity, and the H-Score, respectively. There was no significant relationship between PD-L1 expression and age, gender, smoking, tumor stage and histological subtype (p> 0.05). However, PD-L1 expression was relatively higher in patients <65 years of age, men, smokers, patients with advanced tumor stage, and squamous cell subtype. based on the analysis h-score, no significant difference was noted regarding disease-free survival time between pd-l1 positive negative (median 20 [95% ci 1.2-38.7] months vs. median 27 17.5-36] months, p =0.208). however, overall significantly shorter in compared to 24 9.9-38] 48 33.6-62.3],> Conclusion: In patients with high PD-L1 expression, the biological behavior of the cancer was more aggressive, and the life expectancy was shorter. PD-L1 expression seems to be a poor prognostic marker in NSCLC patients.